PEDAGOGICAL ASPECTS OF CHILDREN’S COOPERATION IN THE COURSE OF TEACHING NATURAL SCIENCE - Ganieva , Gulchachak; Gaifutdinov , Azat; Chirkova, Svetlana; Safina, Aelita (Revista Inclusiones, 2020)
The article is devoted to the formation and development in primary school children of the ability to work in a group (team) by means of creating pedagogical conditions for organizing and conducting a group form work. It presents methods and techniques, criteria for diagnosing the level of these skills. The article substantiates the importance of group work, identifies difficulties in the organization of joint activities of pupils and provides recommendations to overcome them. It uncovers effective methods and techniques of group work organization while studying natural science at primary school. Ggoup work requires a well-thought-out system of actions on the part of a teacher, both at the stage of developing group tasks, and at lessons themselves in the course of organizing them.